Perbaikan Keragaan Bibit Jeruk Pamelo Tanpa Biji dengan Strangulasi dan Aplikasi BAP - Fikrinda, Wahyu ; Agastya, I Made Indra (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
The aim of the research was to study the influence of double strangulation and plant growth regulator BAP (Benzyl Amyno Purine) to increase vegetative growth and improve performance and physiological characteristic of Pummelo (Citrus maxima (Brum.) Merr.) seedling.  The research was conducted from March to Juli 2018 at green house, Tanaman Terpadu Laboratory, Unitri, Malang. Method used for the research was completely randomized design one factor consisted of six treatments: double strangulation with distance between the wire: 10 cm without BAP (J1B0), double strangulation with distance between the wire: 10 cm with BAP 100 ppm (J1B1, double strangulation with distance between the wire: 10 cm with BAP 200 ppm (J1B2), double strangulation with distance between the wire: 15 cm without BAP (J2B0), double strangulation with distance between the wire: 15 cm with BAP 100 ppm (J2B1), double strangulation with distance between the wire: 15 cm with BAP 100 ppm (J2B2). The experiment consisted of three replicates resulted in 18 experimental units. Every experimental unit used 2 plants; thus, total plant used for the experiment was 36 plants. Strangulation treatment was conducted on April 8 and wire removed on June 3, 2018. Research result showed double strangulation with distance between the wire 15 cm had better significant influence on vegetative growth than double strangulation with distance between the wire 10 cm. Double strangulation with distance between the wire 15 cm with BAP 100 ppm was the highest number of leaf (85,83 leaves),the numbers of scion diameter (1.85 cm), number of branch (7.83 branches), total length of branch (156.83 cm),and had significant response increase volume of canopies (307959 cm3).